Pengaruh Penggunaan Internet dan Motivasi Belajar terhadap Hasil Belajar Siswa Akuntansi di Sekolah SMK - Azizul Kholis; Tauada Silalahi; Haikal Rahman; Nadhela Witing Lestari; Kornelius Harefa (Mahesa Research Center, 2022)
This study aims to determine the effect of the internet and learning motivation on student learning outcomes. This research was conducted in the odd semester of the 2021/2022 academic year. The population in this study were all vocational accounting students using the case method at T. Amir Hamzah Private Vocational School in Air Putih District, Batubara Regency, North Sumatra Province. Sampling in this study were as many as 60 students with a quota sampling technique that is taken from each study group. The method of data collection in this research is direct observation, where students are given a questionnaire. The data analysis technique was carried out to determine the effect of the independent variables (X1, X2) on the dependent variable (Y) with multiple linear regression analysis and hypothesis testing. The results showed that there was a positive and significant influence of students' internet use variables on student learning outcomes, there was a positive and significant influence of students' learning motivation variables on student learning outcomes, there was a positive and significant influence simultaneously on the variables of internet use and learning motivation on students' learning outcomes. student learning.